2000
DOI: 10.1148/radiology.217.1.r00oc21115
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Intravascular Signal on Fat-saturated Contrast-enhanced Thoracic MR Arteriograms

Abstract: Intravascular signal intensity loss can be present on contrast-enhanced fat-saturated images of the aortic arch and proximal branch vessels, particularly the left subclavian artery. This phenomenon, which is to the authors' knowledge previously unreported and which is hypothesized to result from undesired water saturation, should not be misinterpreted as stenotic or occlusive vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 11 publications
2
13
0
1
Order By: Relevance
“…The pulse sequence parameters were similar to previously published pulse sequences that have been used for coronary MRA (7, 17). It is noteworthy that, similar to others, we observed cancellation of intravascular signal when combining the pulse sequence used in this study with additional fat saturation (24). To avoid this effect caused by magnetic inhomogeneity in the thorax, we abstained from the use of fat suppression, but rather chose an appropriate inversion delay to suppress most of the background signal of perivascular tissue.…”
Section: Discussionsupporting
confidence: 89%
“…The pulse sequence parameters were similar to previously published pulse sequences that have been used for coronary MRA (7, 17). It is noteworthy that, similar to others, we observed cancellation of intravascular signal when combining the pulse sequence used in this study with additional fat saturation (24). To avoid this effect caused by magnetic inhomogeneity in the thorax, we abstained from the use of fat suppression, but rather chose an appropriate inversion delay to suppress most of the background signal of perivascular tissue.…”
Section: Discussionsupporting
confidence: 89%
“…As a result, a chemically selective fat-saturation technique that targets the expected frequency of fat at a given field strength will fail to fully match the actual frequency of fat in the setting of field inhomogeneity, leading to heterogeneous and poor fat suppression across the field of view (FOV) and possibly even partial suppression of water signal. 13 An alternative approach for suppression of fat signal that may overcome this limitation is to use a Dixon technique in which multiple echoes are obtained using echo times (TEs) with varying relative phases between water and fat. 14Y16 Various postprocessing algorithms may be applied to use the data from the various echoes to determine the relative amounts of water and fat signals contributing to the overall signal within a given voxel.…”
mentioning
confidence: 99%
“…The resonance frequency of the protons in such substances differs from that of protons in free water by 1000-2000 Hz [6,7,8]. A fat-suppression pulse is sometimes observed to reduce the water signal when the static field is inhomogeneous due to the presence of air, bone, high concentrations of Gd contrast agent, or metallic material [3]. The resonance frequency of protons in fat differs from that of free-water protons by 220 Hz at 1.5 T; thus, we hypothesized that an MTC pulse could act as a water-suppression pulse when the B 0 is affected by metallic material.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast-enhanced MRA, it has been reported that a frequency-selective fat-suppression pulse can act as a water-suppression pulse due to magnetic field inhomogeneity, resulting in signal loss in the left subclavian artery [2,3]. In non-contrast-enhanced intracranial 3D-TOF MRA, an MTC pulse is usually employed to suppress the signal from stationary brain tissues [4,5].…”
Section: Introductionmentioning
confidence: 99%